El papel del archivo Políticas e historias de la documentación pública y privada en la Norpatagonia - Pérez, Pilar (Aperturas, 2023)
The investigations gathered in this book reconstruct the histories of the main official documentary archives of North Patagonia, but also of the new archives that have arisen in the sphere of communities, organizations and social groups subordinated in the logic and bureaucracies that marked the formation of those first institutions. The main contribution of the work is the analysis of a central organization to guarantee memory, for the production of research and also -and fundamentally- for the exercise of citizen rights.